Entomopathogenic nematode Steinernema feltiae (Filipjev) (Rhabditida: Steinernematidae) recorded for the first time in Slovenia - Žiga LAZNIK; Timea TÓTH; Tamás LAKATOS; Stanislav TRDAN (Acta Agriculturae Slovenica, 2008)
In Slovenia only recently entomopathogenic nematodes were recorded for the first time. In the beginning of 2007, the presence of Steinernema affine was confirmed. During the further investigations in the same year Steinernema feltiae was recorded on the arable field near Cerknica. In the previous year this field was planted with chicory. In Slovenia, until now the entomopathogenic nematodes had a status of an exotic agents and their use was allowed only in the laboratory experiments. We expect that in Slovenia the use of these biological agents against insect pests will become important alternative to insecticides as it is known in many other countries of the world.